Experimental and Theoretical Study of the Energy Flow of a Two Stages Four Generators Adsorption Chiller - Hadi, Faeza Mahdi (Al-Khwarizmi Engineering Journal, 2019)
This work is concerned with a two stages four beds adsorption chiller utilizing activated carbon-methanol adsorption pair that operates on six separated processes. The four beds that act as thermal compressors are powered by a low grade thermal energy in the form of hot water at a temperature range of 65 to 83 °C. As well as, the water pumps and control cycle consume insignificant electrical power. This adsorption chiller consists of three water cycles. The first water cycle is the driven hot water cycle. The second cycle is the cold water cycle to cool the carbon, which adsorbs the methanol. Finally, the chilled water cycle that is used to overcome the building load. The theoretical results showed that average cycle cooling power is 2.15kW, while the experimental measurement revealed that the cooling capacity of the cycle is about 1.98 kW with a relative error of % 0.02. The generator and condensing temperatures are 83 and 30 °C, respectively. The coefficient of performance (COP) of that chiller was in the range of 0.37 to 0.49. The best operating point and the best working conditions were also investigated. The present chiller is superior more than the single stage, two beds adsorption chiller that works on the activated carbon methanol pair that needs a high ambient temperature.